Genome‐scale metabolic reconstruction and constraint‐based modelling of the Antarctic bacterium Pseudoalteromonas haloplanktis TAC125. (30th June 2014) - Fondi, Marco; Maida, Isabel; Perrin, Elena; Mellera, Alessandra; Mocali, Stefano; Parrilli, Ermenegilda; Tutino, Maria Luisa; Liò, Pietro; Fani, Renato
Summary: The Antarctic strain P seudoalteromonas haloplanktis TAC125 is one of the model organisms of cold‐adapted bacteria and is currently exploited as a new alternative expression host for numerous biotechnological applications. Here, we investigated several metabolic features of this strain through in silico modelling and functional integration of –omics data. A genome‐scale metabolic model of P . haloplanktis TAC125 was reconstructed, encompassing information on 721 genes, 1133 metabolites and 1322 reactions. The predictive potential of this model was validated against a set of experimentally determined growth rates and a large dataset of growth phenotypic data. Furthermore, evidence synthesis from proteomics, phenomics, physiology and metabolic modelling data revealed possible drawbacks of cold‐dependent changes in gene expression on the overall metabolic network of P . haloplanktis TAC125. These included, for example, variations in its central metabolism, amino acid degradation and fatty acid biosynthesis. The genome‐scale metabolic model described here is the first one reconstructed so far for an Antarctic microbial strain. It allowed a system‐level investigation of variations in cellular metabolic fluxes following a temperature downshift. It represents a valuable platform for further investigations on P . haloplanktis TAC125 cellular functional states and for the design of more focused strategies for its possible biotechnological exploitation.